Six big ideas to advance food systems resilience in Nigeria: Bringing CGIAR Initiatives together to foster collaboration and policy coherence - Kosec, Katrina; Kyle, Jordan; Anisimova, Evgeniya; Carrillo, Lucia; Onilogbo, Omobolanle (CGIAR, 2023)
On May 12 in Abuja, Nigeria, two CGIAR initiatives – Fragility, Conflict and Migration (FCM) and National Policies and Strategies for Food, Land and Water Systems Transformation (NPS) – brought together policymakers, researchers, and representatives from the private sector and civil society to discuss how to advance food systems resilience amid crises while empowering women and youth. The workshop invited research presentations from six other CGIAR research initiatives working in Nigeria and facilitated lively discussion among all. Together, workshop participants learned about results from cutting-edge research and identified evidence gaps and possibilities for new collaborations to fill those gaps.